2023
DOI: 10.1111/dom.15121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of Gla‐300 versus IDegAsp in insulin‐naïve people with type 2 diabetes mellitus uncontrolled on oral anti‐diabetics

Abstract: Aim: To compare the efficacy and safety of insulin glargine-300 once daily (Gla-300) with insulin degludec/aspart (IDegAsp) once daily in patients with type 2 diabetes (T2D) inadequately controlled on oral anti-diabetic drugs (OADs). Materials and methods:A systematic literature review of randomized controlled trials was followed by an indirect treatment comparison of studies involving insulin naïve adults, inadequately controlled [glycated haemoglobin (HbA1c) ≥7.0%] on OADs, who received Gla-300 or IDegAsp on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…34 Previous studies have reported that treatment with IDegAsp was associated with increased body weight compared with BI. 35,36 In the current study, iGlarLixi treatment effectively mitigated the body weight gain that is associated with insulin therapy initiation and that was observed with IDegAsp. This difference is probably attributable to the opposite effects on body weight of the GLP-1 RA component in iGlarLixi and the prandial insulin in IDegAsp.…”
Section: Hypoglycaemiamentioning
confidence: 58%
“…34 Previous studies have reported that treatment with IDegAsp was associated with increased body weight compared with BI. 35,36 In the current study, iGlarLixi treatment effectively mitigated the body weight gain that is associated with insulin therapy initiation and that was observed with IDegAsp. This difference is probably attributable to the opposite effects on body weight of the GLP-1 RA component in iGlarLixi and the prandial insulin in IDegAsp.…”
Section: Hypoglycaemiamentioning
confidence: 58%